Total flavonoids isolated from Eucommia ulmoides can alleviate bone loss and regulate intestinal microbiota in ovariectomized rats - Yin, Baocang; Yang, Mingzhen; Wang, Bowen; Zhang, Yun; Li, Ningli; Li, Qin; Li, Yingying; Xian, Cory J.; Li, Tiejun; Zhai, Yuankun (Frontiers in Pharmacology, 2025)
Ethnopharmacological relevanceEucommia ulmoides, recognized as a traditional Chinese medicinal herb, can tonify liver and kidney and strengthen bones and muscles. Modern pharmacological research has proved that E. ulmoides could prohibit the occurrence of osteoporosis and arthritis.AimTo investigate the effect and action mechanism of total flavonoids isolated from the leaves of E. ulmoides (TFEL) on bone loss in ovariectomized (OVX) rats, and to study its effect on intestinal flora.Materials and methodsThe 3-month-old female rats were randomly divided into six groups: sham operation group, OVX model group, estradiol group, TFEL low (TFEL-L) (50), mid (-M) (100) and high (-H) (200 mg/kg/d) dose groups. After 13 weeks of treatment, the rats were sacrificed to measure bone turnover markers, related tissue biochemical indices, microstructure parameters, and osteoclastogenesis promotor RANKL and inhibitor OPG expression levels. Additionally, fecal samples were obtained for high-throughput sequencing to analyze the intestinal flora.ResultsOral administration of TFEL for 13 weeks increased the serum level of bone formation marker PINP and decreased the level of bone resorption marker NTX-I. The femoral microstructure parameters of the TFEL-M and TFEL-H groups were significantly improved compared with the OVX group, which were also confirmed by H&E histological staining. High-throughput sequencing indicated that TFEL may regulate the composition of intestinal flora and intestinal microecology.ConclusionTFEL can prevent osteoporosis in OVX rats and has no toxic side effects. Meanwhile, TFEL can increase the diversity and improve the composition of intestinal flora in OVX rats.